The Formation of Noble Morals Through Religious Activities of Muhammadiyah 2 Elementary School Students at GKB Gresik - Zhafirah Azrin; Noor Amirudin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Moral education is a fundamental aspect of Islamic education aimed at shaping students to be faithful, pious, and behave in accordance with the values of the Qur'an and Hadith. The phenomenon of declining manners and ethics among students toward teachers and the school environment highlights the importance of strengthening character education from an early age through structured habituation. This study aims to describe the role of daily habituation in forming akhlaq mahmudah (commendable moral character) among students at SD Muhammadiyah GKB 2 Gresik. This research employs a qualitative approach using a case study design. Data collection techniques included observation, interviews with classroom teachers and the character habituation coordinator, and documentation of school activities. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that daily habituation implemented consistently and integrated through religious activities and positive habits, such as greeting at the school gate, morning hadith reading, memorization review (murojaah), congregational dhuha prayer, collective dhikr, daily charity (infaq), Qur'anic recitation (tadarus), the 5S culture, and the Klinik Muhasabah Center (KMC) program, contributes to instilling akhlaq mahmudah values in students, particularly discipline, honesty, and responsibility. The role of teachers as role models and the non-corporal punishment approach support the effectiveness of character habituation. The constraint identified was the difference in students' family backgrounds, which affects the continuity of habituation between school and home. Thus, daily habituation plays a strategic role in the formation of students' akhlaq mahmudah and requires ongoing synergy among schools, teachers, and parents.